Tracing the three Atlantic branches entering the Arctic Ocean with 129I and 236U - Casacuberta, Núria; id_orcid:0 000-0001-7316-1655; Christl, Marcus; id_orcid:0 000-0002-3131-6652; Vockenhuber, Christof; Wefing, Anne-Marie; Wacker, Lukas; Masque, Pere; Synal, Hans-Arno; Rutgers van der Loeff, Michiel (Journal of Geophysical Research: Oceans, 2018)
ISSN:0148-0227 ISSN:2169-9275